Libraries Stand Ready as Digital Inclusion Comes of Age - Bryne, Amelia; Janicki, Megan; Visser, Marijke (Maine Policy Review, 2024)
With many small and rural communities and a high percentage of low-income and older residents, Mainers face a variety of barriers to digital inclusion. By sharing stories from this state, we hope to help decision-makers and community leaders in Maine, as well as those across the United States, to gain a deeper understanding of the ways that libraries are embedded in connectivity concerns. Given the depth and breadth of their engagement with digital inclusion work since its inception, libraries stand ready to help the nation adapt to the latest requirements of our digital society—one in which the stakes of being unconnected are increasingly high.